Pneumococcal extracellular vesicles mediate horizontal gene transfer via the transformation machinery - Sarah Werner Lass; Bailey E. Smith; Shaw Camphire; Rory A. Eutsey; Jojo A. Prentice; Saigopalakrishna S. Yerneni; Ashni Arun; Andrew A. Bridges; Jason W. Rosch; James F. Conway; Phil Campbell; N. Luisa Hiller (mSphere)
ABSTRACT Bacterial cells secrete extracellular vesicles (EVs), the function of which is a matter of intense investigation. Here, we show that the EVs secreted by the human pathogen Streptococcus pneumoniae (pneumococcus) are associated with bacterial DNA on their surface and can deliver this DNA to the transformation machinery of competent cells. These findings suggest that EVs contribute to gene transfer in Gram-positive bacteria and, in doing so, may promote the spread of drug resistance genes in the population.IMPORTANCEThis work extends our understanding of horizontal gene transfer and the roles of extracellular vesicles in pneumococcus. This bacterium serves as the model for transformation, a process by which bacteria can take up naked DNA from the environment. Here, we show that extracellular vesicles secreted by the pneumococcus have DNA on their surface and that this DNA can be imported by the transformation machinery, facilitating gene transfer. Understanding EV-mediated gene transfer may provide new avenues to manage the spread of antibiotic drug resistance.